2019
DOI: 10.1097/med.0000000000000511
|View full text |Cite
|
Sign up to set email alerts
|

Impact of circadian rhythms on female reproduction and infertility treatment success

Abstract: Purpose of reviewIn recent years, new studies have investigated the role and influence of sleep on female fertility and early pregnancy outcomes, providing a growing body of knowledge demonstrating how regulation by sleep of hormones are important to reproduction, and how disruptions in sleep, circadian rhythms, and genes regulating circadian rhythmicity can negatively impact fertility and early pregnancy outcomes. This review aims to summarize the most recent research on the relationship among circadian rhyth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…40 Disruption of circadian rhythms has been reported to be associative with poor fertility or even infertility. 41 Interestingly, rhythmic change in expressions F I G U R E 4 Liver FGF21 signaling was involved in the beneficial effect of time-restricted feeding on fertility. WT or FGF21LKO mice were fed with high-fat diet for 24 weeks with or without TRF treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Disruption of circadian rhythms has been reported to be associative with poor fertility or even infertility. 41 Interestingly, rhythmic change in expressions F I G U R E 4 Liver FGF21 signaling was involved in the beneficial effect of time-restricted feeding on fertility. WT or FGF21LKO mice were fed with high-fat diet for 24 weeks with or without TRF treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In humans and mouse, feeding an HFD ad libitum dampens circadian rhythms, thereby causing metabolic damage 40 . Disruption of circadian rhythms has been reported to be associative with poor fertility or even infertility 41 . Interestingly, rhythmic change in expressions of circadian clock components is sustained when diet‐induced obesity mouse is subjected to TRF 8 .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of melatonin on GnRH-induced serum FSH and LH level can demonstrate seasonal variation in reproductive outcome. Circadian dysrhythmia or sleep disturbance can lead to changes in the levels of LH, FSH, and prolactin, which in turn affect the success rate of fertility treatments (15).…”
Section: Discussionmentioning
confidence: 99%
“…An abnormal expression of CLOCK is also detected in human fetuses from spontaneous miscarriage (Li et al 2015). Several epidemiological studies have also suggested a relationship between shift work or repeated travel across time zones and decreased fertility as well as negative pregnancy outcomes such as increased incidence of low birth weight, preterm birth or miscarriage (Reschke et al 2018, Mills & Kuohung 2019, Suzumori et al 2020. Researchers have begun to explore options to alter circadian rhythms to control the timing of birth to prevent poor pregnancy outcomes such as preeclampsia and preterm birth (McCarthy et al 2019).…”
Section: Animals or Subjects Major Implicationsmentioning
confidence: 99%